2016
DOI: 10.1083/jcb.201507122
|View full text |Cite
|
Sign up to set email alerts
|

PML isoform II plays a critical role in nuclear lipid droplet formation

Abstract: PML-II plays a critical role in generating nuclear lipid droplets, which are associated with promyelocytic leukemia nuclear bodies as well as with the extension of the inner nuclear membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
244
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(267 citation statements)
references
References 47 publications
(66 reference statements)
12
244
3
Order By: Relevance
“…It was difficult to distinguish these possibilities using fluorescence microscopy. Recent studies using electron microscopy of serial sections has revealed that LDs may indeed reside within the nucleoplasm [42,44]. Nuclear LDs may be limited to specific cell types.…”
Section: Overview Of the Glycerol 3-phosphate Pathway For Lipid Symentioning
confidence: 99%
See 4 more Smart Citations
“…It was difficult to distinguish these possibilities using fluorescence microscopy. Recent studies using electron microscopy of serial sections has revealed that LDs may indeed reside within the nucleoplasm [42,44]. Nuclear LDs may be limited to specific cell types.…”
Section: Overview Of the Glycerol 3-phosphate Pathway For Lipid Symentioning
confidence: 99%
“…Nuclear LDs may be limited to specific cell types. They have been detected in human liver and human and mouse hepatic cell lines, but are much less abundant in fibroblasts and adipocytes [42,44]. Nuclear LDs appear to localize with protrusions from the inner nuclear cell membrane, and depend on SUN proteins and PML (promyelocytic leukemia) bodies for formation [44].…”
Section: Overview Of the Glycerol 3-phosphate Pathway For Lipid Symentioning
confidence: 99%
See 3 more Smart Citations